2017
DOI: 10.5007/2175-8026.2017v70n3p201
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Training in Shaping Teacher Cognition Related to L2 Pronunciation

Abstract: This study analyzed changes in the pronunciation-related cognitions of undergraduate TESL students from two Canadian universities during their first term in their programs. The students from one university attended a 13-week course in phonology and pronunciation teaching, while those from the other university received no specific training in pronunciation. Towards the end of the term, the participants who received specialized training had more favorable views of explicit pronunciation teaching and became more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 32 publications
3
20
0
1
Order By: Relevance
“…Through the course of their study, they began to perceive themselves as credible teachers of English pronunciation. From a teacher cognition perspective -typically examining practitioners' beliefs, knowledge, thoughts, perceptions, and attitudes (Borg, 2006;Burns, Freeman, & Edwards, 2015) -Buss' (2017 work demonstrated the impact of an undergraduate pronunciation teacher training course on pre-service teachers' cognition, including an increase in "confidence in their ability to teach pronunciation" (p. 217). Prior to Buss' research, Baker's (2011a) study revealed a positive relationship between learning to teach pronunciation in a graduate program and instructors' cognition and classroom practices.…”
Section: Second Language Teacher Education and Pronunciation Teacher mentioning
confidence: 99%
“…Through the course of their study, they began to perceive themselves as credible teachers of English pronunciation. From a teacher cognition perspective -typically examining practitioners' beliefs, knowledge, thoughts, perceptions, and attitudes (Borg, 2006;Burns, Freeman, & Edwards, 2015) -Buss' (2017 work demonstrated the impact of an undergraduate pronunciation teacher training course on pre-service teachers' cognition, including an increase in "confidence in their ability to teach pronunciation" (p. 217). Prior to Buss' research, Baker's (2011a) study revealed a positive relationship between learning to teach pronunciation in a graduate program and instructors' cognition and classroom practices.…”
Section: Second Language Teacher Education and Pronunciation Teacher mentioning
confidence: 99%
“…ESL/EFL preservice teachers often start their teaching education coursework with a naïve understanding of teaching and learning. However, it is important to note that the studies reviewed in this paper revealed a significant effect of teacher education coursework and academic preparation on developing preservice teachers' cognitions (Albaba, 2017;Amory;2020, Burri, 2015Buss, 2017;Çimen & Daloğlu, 2019;Da Silva, 2005;Guerrettaz et al, 2020;Šipošová, 2021;Tang, Lee & Chun, 2012;Wong, 2010). Of great significance here is what AlBaba (2017) revealed regarding the long-term impact of teacher education coursework on EFL preservice teachers.…”
Section: The Effect Of Teacher Education In Shaping Esl/efl Pre-servi...mentioning
confidence: 59%
“…Finally, Buss (2017) explained that undergraduate TESL students in two Canadian universities, who received explicit instruction on how to teach pronunciation, became more confident about their ability to teach the subject and cognizant of their speech limitations. Equally important is the fact that interactions between the native English speaking student teacher group and the nonnative English speaking student teacher group helped the latter in their cognitive development.…”
Section: The Effects Of Practicum On Esl/efl Preservice Teacher Cogni...mentioning
confidence: 99%
See 1 more Smart Citation
“…Para la segunda alternativa (competencia oral, pronunciación), los informantes proponen soluciones del tipo "escuchar y hablar más; más canciones o conversaciones en inglés" (estudiante 4, comunicación personal, 12 de febrero de 2020). Por lo tanto, reclaman formación especializada en la enseñanza de la lengua oral y, sobre todo, la pronunciación (Buss, 2017). Finalmente, un estudiante hace referencia a cuestiones de corte pedagógico y no solo idiomático: "el profesor no solo tiene que tener conocimiento de la lengua, sino también saber dar clase y adaptarse a las necesidades de los alumnos" (estudiante 5, comunicación personal, 14 de febrero de 2020), algo ya anticipado en esta área de investigación (Chong, Cho, Wong, 2005;Ramanayake & Williams;2017).…”
Section: Lack Of Foreign Language Competenceunclassified